Globalization, Economic Shocks, and Internal Armed Conflict - Elbadawi, Ibrahim; Hegre, Havard (2012)
Critics of trade liberalization argue that globalization increases countries' vulnerability to economic shocks and hence may exacerbate domestic social conflict. Such social conflict may also be transformed into armed conflict. Others argue that globalization promotes economic growth and reduces poverty, which leads to a reduction in the risk of internal conflict. Several studies find trade to reduce the risk of interstate conflict. This article investigates the impact of trade and trade shocks on the risk of intrastate conflict. A set of operationalizations of economic shock is developed and used to analyze the risk of conflicts that involve at least 25 battle deaths per year. The analysis finds no robust evidence for a direct relationship between trade openness, trade shocks, and the risk of armed conflict. There is somewhat more basis for concluding that globalization affects the risk indirectly through its effect on long- and short-term growth. In the long run, trade-induced growth reduces the risk of domestic conflict.